2020
DOI: 10.1186/s12968-020-00608-0
|View full text |Cite
|
Sign up to set email alerts
|

4D flow cardiovascular magnetic resonance for monitoring of aortic valve repair in bicuspid aortic valve disease

Abstract: Background: Aortic valve repair has become a treatment option for adults with symptomatic bicuspid (BAV) or unicuspid (UAV) aortic valve insufficiency. Our aim was to demonstrate the feasibility of 4D flow cardiovascular magnetic resonance (CMR) to assess the impact of aortic valve repair on changes in blood flow dynamics in patients with symptomatic BAV or UAV. Methods: Twenty patients with adult congenital heart disease (median 35 years, range 18-64; 16 male) and symptomatic aortic valve regurgitation (15 BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…Four-dimensional phase contrast magnetic resonance imaging (4D flow MRI) is an advanced imaging technique, which allows for acquisition of morphological images and velocity data. 4D flow MRI thus enables visualization and quantification of complex blood flow patterns in the thoracic aorta [ 12 , 13 ]. Recent 4D flow MRI studies showed promising results in Marfan patients supporting the notion that pathological blood flow profiles may contribute to aneurysm formation [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four-dimensional phase contrast magnetic resonance imaging (4D flow MRI) is an advanced imaging technique, which allows for acquisition of morphological images and velocity data. 4D flow MRI thus enables visualization and quantification of complex blood flow patterns in the thoracic aorta [ 12 , 13 ]. Recent 4D flow MRI studies showed promising results in Marfan patients supporting the notion that pathological blood flow profiles may contribute to aneurysm formation [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 4D flow MRI visualizes complex hemodynamic changes, eg vortices and helices, or eccentric flow. 24,25 Particularly with respect to the fetus, 4D flow MRI has several advantages over 2D phase-contrast MRI and echocardiography as it enables retrospective definition of the relevant target vessels within the acquired 3D volume with operator-independent offline analysis. Our initial results indicate that fetal aortic DUS-gated 4D flow MRI is feasible for the assessment of aortic hemodynamics including the aortic isthmus, revealing physiological flow patterns in our three healthy fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Four‐dimensional flow MRI is an emerging technique that allows time‐resolved co‐registration of both morphological and hemodynamic information in a 3D volume over the whole cardiac cycle. The 4D flow MRI visualizes complex hemodynamic changes, eg vortices and helices, or eccentric flow 24,25 . Particularly with respect to the fetus, 4D flow MRI has several advantages over 2D phase‐contrast MRI and echocardiography as it enables retrospective definition of the relevant target vessels within the acquired 3D volume with operator‐independent offline analysis.…”
Section: Discussionmentioning
confidence: 99%
“…WSS estimates are influenced by the exact placement of the region of interest and by the chosen spatial resolution [62]. However, the relative intra-and interindividual distribution of WSS estimates might be reasonably accurate [5,35]. In the abdominal aorta, elevated WSS was described adjacent to the ostia of the renal arteries in healthy volunteers [63].…”
Section: Abdominal Aorta and Mesenteric Arteriesmentioning
confidence: 99%
“…Four-dimensional flow magnetic resonance imaging (4D flow MRI) is a three-dimensional and time-resolved phase contrast imaging technique allowing characterization of blood flows within the entire vasculature [1][2][3]. 4D flow MRI enables the visualization of physiological and pathological flow patterns by registration of both morphology and velocity data [3][4][5].…”
Section: Introductionmentioning
confidence: 99%